From a state to a trait: Trajectories of state mindfulness in meditation during intervention predict changes in trait mindfulness - Kiken, Laura G.; Garland, Eric L.; Bluth, Karen; Palsson, Olafur S.; Gaylord, Susan A. (Personality and individual differences, 2015)
•We assessed state mindfulness in meditation weekly during a mindfulness intervention.•Individuals’ rates of change in state mindfulness in meditation varied significantly.•These individual trajectories predicted pre-post changes in trait mindfulness.•They also directly and indirectly predicted changes in psychological distress. Theory suggests that heightening state mindfulness in meditation practice over time increases trait mindfulness, which benefits psychological health. We prospectively examined individual trajectories of state mindfulness in meditation during a mindfulness-based intervention in relation to changes in trait mindfulness and psychological distress. Each week during the eight-week intervention, participants reported their state mindfulness in meditation after a brief mindfulness meditation. Participants also completed pre- and post-intervention measures of trait mindfulness and psychological symptoms. Tests of combined latent growth and path models suggested that individuals varied significantly in their rates of change in state mindfulness in meditation during the intervention, and that these individual trajectories predicted pre-post intervention changes in trait mindfulness and distress. These findings support that increasing state mindfulness over repeated meditation sessions may contribute to a more mindful and less distressed disposition. However, individuals’ trajectories of change may vary and warrant further investigation.